Ethylene / octylene multi-block copolymer and preparation method thereof
By contacting ethylene and octene with a specific catalyst system at high temperature, a high content normalized OOO triple ethylene/octene multi-block copolymer is formed, which solves the problems of low-density soft block limiting factors and poor solid treatment performance in the prior art, and achieves better fluidity and treatment characteristics.
Patent Information
- Application Number
- CN202411429178.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-27
- Filing Date
- 2020-12-23
- Publication Date
- 2025-03-18
AI Technical Summary
Existing ethylene/octene multiblock copolymers have low density soft block limiting factors in mass production and storage of particles, and have poor solid handling performance, especially high unconstrained yield strength.
At a temperature above 125°C, ethylene and octene are contacted with a catalyst system containing the first and second polymerization catalysts and chain shuttle agents of a specific structure to form an ethylene/octene multiblock copolymer with a normalized OOO triple content greater than 0.25.
The incorporation amount of soft-segment octene and solid treatment performance are improved, especially the unconstrained yield strength is reduced, and the fluidity and treatment characteristics of the polymer are improved.
Smart Images

Figure CN119638926A_ABST
Abstract
Description
[0001] This invention application is a divisional application based on the invention patent application with application date of December 23, 2020, application number 202080092825.4 (international application number PCT / US2020 / 066896) and name “Ethylene / octene multi-block copolymer and preparation method thereof”. Background Art
[0002] Ethylene / octene multi-block copolymers provide the advantages of durability and high temperature resistance of high-density polyethylene, while maintaining the key characteristics of elastic low-density polyolefins (such as elasticity, flexibility and processability). Typically, ethylene / octene multi-block copolymers include high-density "hard" segments and low-density "soft" segments. The soft segments contain a higher content of comonomers, which may be soft and easy to adhere to. For the commercial production of ethylene / octene multi-block copolymers that are valuable for bulk transportation, low-density soft blocks are limiting factors for large-scale production and storage of particles. Many applications can benefit from lower density soft blocks (more octene incorporated), but existing ethylene / octene multi-block copolymer systems are limited due to poor solids handling.
[0003] There is a recognized need in the art for an ethylene / octene multi-block copolymer having increased soft segment octene incorporation and improved solids handling properties, particularly improved (lower) unconstrained yield strength. Summary of the invention
[0004] The present disclosure provides a method. In one embodiment, the method includes contacting ethylene and octene with a catalyst system under polymerization conditions at a temperature greater than 125° C., the catalyst system comprising (i) a first polymerization catalyst having a structure of formula (III), (ii) a second polymerization catalyst having a structure of formula (I), and (iii) a chain shuttling agent. The method includes forming an ethylene / octene multi-block copolymer having a normalized OOO triad content greater than 0.25.
[0005] The present disclosure provides the resulting composition produced by the method.In one embodiment, the composition includes an ethylene / octene multi-block copolymer having a normalized OOO triad content greater than 0.25. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] Figure 1 is a graph showing the extrapolation of elution temperature for TGIC temperature calibration. The solid line represents experimental data. The dashed line represents the extrapolation of the elution temperature for two isothermal steps.
[0007] Figure 2is a graph showing the correlation of the elution peak temperature (Tp) of ethylene-octene copolymers prepared by a single site catalyst with respect to octene wt%. High temperature thermal gradient interaction chromatography (TGIC) was measured according to reference (Cong et al., Macromolecules, 2011, 44(8), 3062-3072), which is incorporated herein by reference. As disclosed in U.S. Pat. No. 7,608,668, by 13 C NMR measures octene content, which is incorporated herein by reference.
[0008] Figure 3 is a schematic diagram of a test apparatus for funnel flow (FF). The FF test apparatus consists of a steep glass funnel attached to a cylinder (4.15 inches in diameter). The cylindrical portion provides the necessary capacity so that a large number of particles can be tested.
[0009] Figure 4 is a graph showing the second peak temperature (T) of high temperature thermal gradient interaction chromatography (TGIC) of the inventive examples and comparative samples of the ethylene / octene multi-block copolymers according to the embodiments of the present disclosure. p2 ) as a function of the soft segment melting temperature (SS-Tm), i.e., showing the relationship between the second peak temperature of TGIC and the soft segment melting temperature measured by DSC. Figure 4 The line in is given by the equation: P2 =0.0068*(SS-T m ) 2 +0.7*(SS-T m )+73.2. For the embodiments of the present invention, T P2 ≤0.0068*(SS-T m ) 2 +0.7*(SS-T m )+73.2, where SS-Tm is -30℃ to 30℃. TGIC T P2 is the peak temperature of the second peak in the TGIC heating curve, and SS-Tm is the melting temperature of the soft segment obtained from the second DSC heating curve, respectively. Figure 5 and Figure 6 shown.
[0010] Figure 5 is a graph showing the first peak temperature (T p1 ) and the second peak temperature (T p2 )’s TGIC curve.
[0011] Figure 6 is a DSC heating curve showing the soft segment melting peak of Inventive Example 1 according to an embodiment of the present disclosure.
[0012] Figure 7 is a graph showing the soft segment melting temperature (SS-Tm) as a function of normalized OOO triads for inventive examples and comparative samples of ethylene / octene multi-block copolymers according to embodiments of the present disclosure, i.e., showing the relationship between the soft segment Tm measured by DSC and the normalized OOO triad content measured by NMR.
[0013] Figure 8 is a graph showing the glass transition temperature (Tg) as a function of normalized OOO triad content for inventive examples and comparative samples of ethylene / octene multi-block copolymers according to embodiments of the present disclosure, i.e., showing T as measured by DSC versus normalized OOO triad content as measured by NMR. like Figure 7 and Figure 8 As shown, for the embodiments of the present invention, the normalized OOO triad content measured by NMR is >0.25, T g In the range of -55℃ to -70℃, and for the soft segment T m In the range of -30℃ to 30℃.
[0014] definition
[0015] Any reference to the Periodic Table of the Elements is to the Periodic Table as published by CRC Press, Inc., 1990-1991. A group of elements in this table is referred to by a new notation for numbering the groups.
[0016] For purposes of U.S. patent practice, the contents of any cited patent, patent application, or publication, particularly with respect to disclosure of definitions (to the extent not inconsistent with any definitions specifically provided in this disclosure) and general knowledge in the art, are incorporated by reference in their entirety (or their equivalent U.S. versions are also so incorporated by reference).
[0017] Numerical ranges disclosed herein include all values from the lower limit to the upper limit, and include the lower limit and the upper limit. For ranges containing explicit values (e.g., 1 or 2 or 3 to 5 or 6 or 7), any subrange between any two explicit values is included (e.g., above range 1-7 includes subranges 1 to 2; 2 to 6; 5 to 7; 3 to 7; 5 to 6; etc.).
[0018] Unless stated to the contrary, implicit from the context, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.
[0019] As used herein, the term "blend" or "polymer blend" is a blend of two or more polymers. The blend may or may not be miscible (not phase separated at the molecular level). The blend may or may not be phase separated. The blend may or may not contain one or more domain configurations, as determined by transmission electron spectroscopy, light scattering, x-ray scattering, and other methods known in the art.
[0020] The term "composition" refers to a mixture of materials comprising the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0021] The terms "comprising", "including", "having" and their derivatives are not intended to exclude the presence of any additional components, steps or procedures, whether or not the components, steps or procedures are specifically disclosed. For the avoidance of any doubt, unless stated to the contrary, all compositions claimed by using the term "comprising" may include any additional additives, adjuvants or compounds, whether in polymeric form or otherwise. In contrast, the term "consisting essentially of excludes any other components, steps or procedures (except those that are not essential to operability) from the scope of any subsequent statements. The term "consisting of" excludes any components, steps or procedures that are not specifically described or listed. Unless otherwise stated, the term "or" refers to the listed members individually and in any combination. The use of the singular includes the use of the plural, and vice versa.
[0022] "Ethylene polymers" are polymers that contain more than 50 weight percent (wt%) polymerized ethylene monomer (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Ethylene-based polymers include ethylene homopolymers and ethylene copolymers (meaning units derived from ethylene and one or more comonomers). The terms "ethylene polymers" and "polyethylene" are used interchangeably.
[0023] "Interpolymer" is a polymer prepared by polymerizing at least two different monomers. This general term encompasses copolymers, usually employed to refer to polymers prepared from two different monomers, and polymers prepared from more than two different monomers, for example, terpolymers, tetrapolymers, and the like.
[0024] "Olefin polymers" or "polyolefins" are polymers containing more than 50 weight percent polymerized olefin monomers (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Non-limiting examples of olefin polymers include ethylene polymers and propylene polymers.
[0025] "Polymer" is a compound prepared by polymerizing monomers of the same or different types, which provide multiple and / or repeated "units" or "monomer units" constituting the polymer in a polymerized form. Therefore, the general term polymer covers the term homopolymer, which is usually used to refer to polymers prepared from only one type of monomer, and the term copolymer, which is usually used to refer to polymers prepared from at least two types of monomers. It also covers all forms of copolymers, such as random copolymers, block copolymers, etc. The terms "ethylene / α-olefin polymer" and "propylene / α-olefin polymer" represent copolymers prepared by polymerizing ethylene or propylene and one or more other polymerizable α-olefin monomers, respectively, as described above. It should be noted that although polymers are usually referred to as "made of" one or more specified monomers, "based on" a specified monomer or monomer type, "containing" a specified monomer content, etc., in this context, the term "monomer" should be understood to refer to the polymerized residue of the specified monomer rather than the unpolymerized substance. Generally, the polymers herein are referred to as "units" based on the polymerized form of the corresponding monomers.
[0026] Test Method
[0027] 13 C NMR
[0028] The 13C NMR spectra were prepared by adding approximately 2.7 g of a 50 / 50 by weight mixture of tetrachloroethane-d2 / o-dichlorobenzene containing 0.025 M chromium acetylacetonate and Cr(AcAc)3 (or tetrachloroethane-d2 containing 0.025 M Cr(AcAc)3) to 0.2 g of the polymer sample in a 10 mm NMR tube. 13 C NMR) samples. Oxygen was removed from the samples by purging the tube headspace with nitrogen. The samples were then dissolved and homogenized by heating the tube and its contents to 135° C. using a heating block and a heat gun. Each dissolved sample was visually inspected to ensure homogeneity.
[0029] The samples were collected on a Bruker 400 MHz or 600 MHz spectrometer using a 10 mm cryoprobe. 13 C NMR data. The data were acquired at a sample temperature of 120°C using a 7.3 second pulse repetition delay, a 90 degree flip angle, and inverse gated decoupling. All measurements were performed in locked mode on non-spinning samples. The samples were allowed to thermally equilibrate for 7 minutes before data acquisition. 13 C NMR chemical shifts were internally referenced to the EEE triad at 30.0 ppm.
[0030] The comonomer content was calculated using the distribution and integration of references (Liu, W., Rinaldi, PL, McIntosh, LH, and Quirk, RP, Macromolecules, 34, 2001, 4757-4767). 13 C NMR spectrum is determined to solve the vector equation s=fM, where M is the distribution matrix, s is the row vector representation of the spectrum, and f is the mole fraction composition vector. The elements of f are regarded as triplets of E and O with all arrangements of ethylene (E) and octene (O). The distribution matrix M is created as a row for each triplet in f, and a column for each integral NMR signal. The elements of the matrix are integral values determined by reference distribution (Liu, W., Rinaldi, PL, McIntosh, LH, and Quirk, RP, "Macromolecules", 34, 2001, 4757-4767). The equation is solved by changing the elements of f as needed to minimize the integral of s and each sample. 13 The error function between the C data. This is performed using the Solver function in Microsoft Excel.
[0031] EOE / 1000C, EOO(OOE) / 1000C and OOO / 1000C are measured by first setting the integration from 8-46ppm to 1000, and then measuring the integration of the methine peaks at about 38.2ppm for EOE, about 35.9ppm for EOO(OOE) and about 33.7ppm for OOO. Total O / 1000C is defined as EOE / 1000C+EOO(OOE) / 1000C+OOO / 1000C. The term "1000C" is 1000 carbon atoms, and the term " / 1000C" is per 1000 carbon atoms. "OOO percentage" (or "OOO%") is defined as OOO%=100*(OOO / 1000C) / (total O / 1000C). "Normalized OOO content" (Norm OOO) is defined as (OOO%) / (NMR O mol%).
[0032] Density is measured according to ASTM D792 Method B. Results are reported in grams per cubic centimeter (g / cc).
[0033] Differential Scanning Calorimetry (DSC)
[0034] Differential Scanning Calorimetry (DSC) can be used to measure the melting, crystallization, and glass transition behavior of polymers over a wide temperature range. For example, a TA Instruments Discovery DSC equipped with a refrigerated cooling system (RCS) and an autosampler was used to perform this analysis. During the test, a nitrogen purge gas flow of 50 ml / min was used. Each sample was melt pressed into a film at about 190°C; the molten sample was then air cooled to room temperature (about 25°C). A 3-10 mg 6 mm diameter specimen was extracted from the cooled polymer, weighed, placed in a light aluminum pan (approximately 50 mg), and crimped closed. The analysis was then performed to determine its thermal properties.
[0035] The thermal behavior of the sample is determined by ramping the sample temperature up and down to produce a heat flow versus temperature curve. First, the sample is rapidly heated to 180°C and held isothermally for 5 minutes to remove its thermal history. Next, the sample is cooled to -90°C at a 10°C / minute cooling rate and held isothermally at -90°C for 5 minutes. Next, the sample is heated to 150°C at a 10°C / minute heating rate (this is the "second heating" ramp). The cooling curve and the second heating curve are recorded.
[0036] The soft segment melting temperature SS-Tm is determined from the DSC second heating curve. Typically, ethylene / octene multi-block copolymers have two melting peaks, one of which is associated with each of the soft segment and the hard segment. The SS-Tm is associated with the lower temperature peak, such as Figure 6As shown. For some block copolymers, the peak associated with the melting of the soft segment is a small peak (or bump) on the baseline, making it difficult to assign the maximum peak. This difficulty can be overcome by converting the ordinary DSC curve into a weighted DSC curve using the following method. In DSC, the heat flow depends on the amount of material that melts at a specific temperature and the temperature-dependent specific heat capacity. The temperature dependence of the specific heat capacity in the molten state of linear low density polyethylene causes the heat of fusion to increase with decreasing comonomer content. That is, as the comonomer content increases, the crystallinity decreases and the heat of fusion value gradually decreases. See Wild, L. Chang, S. and Shankernarayanan, M J. for an improved method for analyzing polyolefin composition using DSC. Polym. Prep 1990; 31: 270-1, the entire text of which is incorporated herein by reference. For a given point in the DSC curve (defined by heat flow in Watts / gram and temperature in degrees Celsius), the DSC curve can be converted into a weight-dependent distribution curve by taking the ratio of the expected heat of fusion for the linear copolymer to the temperature-dependent heat of fusion (ΔH(T)). The second heating curve is baseline corrected by drawing a linear baseline between the heat flow at -30°C and 135°C. The temperature-dependent heat of fusion curve can then be calculated from the sum of the integrated heat flow between two consecutive data points and then represented overall by a cumulative enthalpy curve. The expected relationship between the heat of fusion of linear ethylene / octene copolymers at a given temperature is shown by the heat of fusion versus melting temperature curve. By using a random ethylene / octene copolymer, the expected heat of fusion ΔH for a linear copolymer can be obtained. 线性共聚物 and melting temperature T m (in °C) is the following relationship:
[0037]
[0038] For each integrated data point at a given temperature, a fractional weight can be assigned to each point of the DSC curve by taking the ratio of the enthalpy value of the cumulative enthalpy curve to the expected heat of fusion for a linear copolymer at that temperature. This method is applicable to ethylene / octene copolymers but can also be applied to other polymers. The soft segment Tm is assigned as the location of the maximum value in the enthalpy fractional weight versus temperature curve.
[0039] The glass transition temperature, Tg, is determined from the DSC second heating curve in which half of the sample has obtained the liquid heat capacity, as described in Bernhard Wunderlich, The Basis of Thermal Analysis, in Thermal Characterization of Polymeric Materials 92, 278-279 (Edith A. Turi, ed., 2nd ed., 1997). Baselines are drawn from below and above the glass transition region and extrapolated through the Tg region. The temperature at the midpoint between these baselines is the Tg.
[0040] The melting point, Tm, of a polymer is determined as the temperature corresponding to the maximum heat flow in the DSC heating curve.
[0041] Elastic recovery rate
[0042] Use with Instron TM The 100% and 300% hysteresis were determined from cyclic loading of the instrument's ASTM D 1708 microtensile specimens to 100% and 300% strain. The specimens were loaded and unloaded for 3 cycles at 267% / min at 21°C. In the 300% strain cyclic experiment, the contraction stress at 150% strain from the first unloading cycle was recorded. The percent recovery for all experiments was calculated after the first unloading cycle using the strain that returned the load to the baseline. The percent elastic recovery is defined as:
[0043]
[0044] Among them, ε f is the maximum strain for cyclic loading and ε s is the strain at which the load returns to the baseline during the first unloading cycle.
[0045] Funnel flow
[0046] The Funnel Flow or "FF" test quantifies interparticle stickiness and is based on the basic concept that increased interparticle interactions (stickiness) will reduce the discharge rate of a steep funnel. Changes in discharge rate can be related to changes in the surface properties (ie, stickiness) of the polymer particles.
[0047] Test equipment (see Figure 3 ) consists of a steep glass funnel attached to a cylinder (4.15 inches in diameter). The cylindrical portion provides the necessary capacity to allow a large number of particles to be tested and to avoid the problem of distinguishing small discharge time values. For statistical purposes, the test was repeated five times.
[0048] The discharge rate of the granules was measured against a commercial reference "as is", the inventive examples (granules) were coated with talc before measurement. The granules were conditioned at a predetermined storage temperature for a predetermined duration. The granules were "heat treated" or "aged" for three weeks at 42°C. The conditioned granules were cooled overnight at 21°C to reach a constant temperature.
[0049] As described above, the polymer (about 2500 g; in pellet form; 30 ± 10 pellets per gram) was heat treated in an oven at 42°C for three weeks. The polymer was recovered from the oven and cooled at 21°C for 12 hours. The polymer pellets (2500 g) were loaded into a funnel, the time for the pellets to be completely discharged from the funnel was measured, and the discharge rate was calculated using the following equation.
[0050]
[0051] Funnel flow is an indicator of the stickiness of the particles and is measured in grams per second (g / s). It has been determined that a flowability of 120 g / s is the minimum flow rate required to achieve acceptable handling characteristics for polymer particles. However, higher rates are preferred to better handle the polymer particles. The higher the particle flowability value, the freer the particles flow and the less sticky they are.
[0052] Coating the particles with talc
[0053] The particles to be coated are placed in a sealed bag. The size of the bag is such that it is approximately half filled with particles to ensure proper mixing. The amount of coating agent (talc) required to coat the particles to the desired ppm level is calculated using the following equation:
[0054] Weight of coating material (gm) = Weight of particles (gm) x desired coating level (ppm) / 1,000,000
[0055] Weigh the amount of coating material using a 4-decimal balance and divide into 4 equal portions. Take the first portion (1 / 4 of the coating material) and sprinkle it on the surface of the particles in the sealed bag. Fill the bag with air and mix the particles thoroughly by shaking them back and forth for 30 seconds. Repeat the above steps for the remaining 3 portions.
[0056] Thermal Gradient Interaction Chromatography (TGIC).
[0057] High temperature thermal gradient interaction chromatography (HT-TGIC or TGIC) measurements were performed using a commercially available crystallization elution fractionation instrument (CEF) (Polymer Char, Spain) (Cong et al., Macromolecules, 2011, 44(8), 3062-3072). The CEF instrument was equipped with an IR-4 detector or an IR-5 detector. Graphite has been used as a stationary phase in HT TGIC columns (Freddy, A. Van Damme et al., U.S. Pat. No. 8,476,076; Winniford et al., U.S. Pat. No. 8,318,896). A single graphite column (250×4.6 mm) was used for separation. Graphite was filled into the column using a dry packing technique prior to a slurry packing technique as disclosed in European Patent EP 2714226B1, the contents of which are incorporated herein by reference. The experimental parameters were: top oven / transfer tube / needle temperature of 150°C, dissolution temperature of 150°C, dissolution agitation setting of 2, pump stabilization time of 15 seconds, pump flow rate for column cleaning of 0.500 mL / m, pump flow rate for column loading of 0.300 mL / min, stabilization temperature of 150°C, stabilization time (pre, before loading into the column) of 2.0 minutes, stabilization time (post, after loading into the column) of 1.0 minutes, SF (soluble fraction) time of 5.0 minutes, cooling rate from 150°C to 30°C of 3.00°C / min, flow rate during cooling process of 0.04 mL / min, heating rate from 30°C to 160°C of 2.00°C / min, isothermal time at 160°C of 10 minutes, elution flow rate of 0.500 mL / min and injection loop size of 200 microliters.
[0058] The flow rate during cooling was adjusted according to the length of the graphite column so that all polymer fractions must remain on the column at the end of the cooling cycle.
[0059] The sample was prepared by a PolymerChar autosampler at a concentration of 4.0 mg / mL in ODCB (defined below) at 150°C for 120 minutes. Silica gel 40 (particle size 0.2-0.5 mm, catalog number 10181-3, EMD) was dried at 160°C in a vacuum oven for about two hours before use. 2,6-di-tert-butyl-4-methylphenol (1.6 g, BHT, catalog number B1378-500G, Sigma-Aldrich) and silica gel 40 (5.0 g) were added to two liters of o-dichlorobenzene (ODCB, 99% anhydrous grade, Sigma-Aldrich). For CEF instruments equipped with an autosampler with N2 purge capability, silica gel 40 was filled into three 300x7.5mm GPC-sized stainless steel columns, and the silica gel 40 columns were installed at the inlet of the pump of the CEF instrument to dry the ODCB; and BHT was not added to the mobile phase. This "ODCB containing BHT and silica gel" or ODCB dried with silica gel 40 is now referred to as "ODCB". TGIC data were processed on the PolymerChar (Spain) "GPCOne" software platform. Temperature calibration was performed with a mixture of about 4mg to 6mg of eicosane, 14.0mg of isotactic homopolymer polypropylene ("iPP") (polydispersity of 3.6 to 4.0, molecular weight Mw reported as polyethylene equivalent 150,000 to 190,000, and polydispersity (Mw / Mn) of 3.6 to 4.0), wherein the iPP DSC melting temperature was measured to be 158-159°C (DSC method described below). In a 10 mL vial containing 7.0 mL ODCB was added 14.0 mg of polyethylene homopolymer HDPE (comonomer content zero, weight average molecular weight (Mw) of 115,000 to 125,000 based on polyethylene equivalent, and polydispersity of 2.5 to 2.8). Dissolution time was 2 hours at 160°C.
[0060] A solution of eicosane and HDPE was used in the calibration process. For elution temperatures in the range of 30°C to 150°C, the process consisted of the following steps:
[0061] 1. Infer the elution temperature of each isothermal step in the elution process based on the heating rate (e.g. Figure 1 shown).
[0062] 2. Calculate the delay volume. The temperature (x-axis) is offset corresponding to the IR measurement channel chromatogram (y-axis) so that the maximum peak of eicosane (y-axis) coincides with the elution temperature at 30.0°C. The delay volume is calculated by dividing the temperature difference (30°C - actual elution temperature of the maximum peak of eicosane) by the heating rate of the method and then multiplying by the elution flow rate.
[0063] 3. Use this same delay volume adjustment for each recorded elution temperature.
[0064] 4. The heating rate was linearly scaled so that the HDPE reference was observed to have an elution peak maximum temperature of 150.0 °C, while the eicosane elution peak maximum temperature remained at 30.0 °C.
[0065] At least 20 ethylene octene random copolymers have been prepared using single site catalysts having Mw (ethylene equivalent weight average molecular weight) ranging from 36,000 to 150,000 and polydispersity of 2.0-2.2. The measured elution peak temperature (Tp) of each ethylene octene copolymer and the octene content (wt%) of the copolymer follow Figure 2 The dependencies specified in .
[0066] Data processing for the high temperature TGIC polymer samples is described below.
[0067] A solvent blank (pure solvent injection) was run under the same experimental conditions as the polymer samples. Data processing for the polymer samples included: subtraction of the solvent blank for each detector channel, temperature extrapolation as described in the calibration procedure, temperature compensation with the delay volume determined by the calibration procedure, and adjustment of the elution temperature axis to the range of 30°C and 160°C as calculated from the calibrated heating rate.
[0068] The chromatograms (measurement channels of the IR-4 detector or IR-5 detector) are integrated with PolymerChar's "GPC One" software. A straight baseline is drawn from the visible difference when the peaks are reduced to a flat baseline at high elution temperature (subtracting the approximate zero value in the blank chromatogram) and the minimum or flat area of the detector signal on the high temperature side of the soluble fraction (SF). For some ethylene / octene multi-block copolymers of the present disclosure, the TGIC chromatogram contains three peaks, such as Figure 5 As shown. p1 is the elution temperature of the maximum peak corresponding to the highest temperature elution peak. p2 is the elution temperature corresponding to the maximum peak of the second highest temperature eluting peak.
[0069] DSC method for measuring the melting temperature of polypropylene homopolymers specified in HT-TGIC.
[0070] Melting point is determined using differential scanning calorimeter (DSC). The temperature at the maximum heat flow rate relative to the linear baseline is used as the melting point. The linear baseline is constructed from the beginning of melting (above the glass transition temperature) to the end of melting. The temperature is raised from room temperature to 200°C at a rate of 10°C / min, kept at 200°C for 5 minutes, reduced to 0°C at a rate of 10°C / min, kept at 0°C for 5 minutes, then raised from 0°C to 200°C at a rate of 10°C / min, and data is obtained from this second heating cycle.
[0071] Triple Detector GPC (TD-GPC)
[0072] The chromatographic system for triple detector gel permeation chromatography (TD-GPC) consists of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven chamber is set to 160°C and the column chamber is set to 150°C. The columns used are 4 Agilent "Mixed A" 30cm 20 micron linear mixed bed columns and 20um pre-columns. The chromatographic solvent used is 1,2,4 trichlorobenzene and contains 200ppm of butylated hydroxytoluene (BHT). The solvent source is nitrogen sparged. The injection volume used is 200 microliters and the flow rate is 1.0 ml / min.
[0073] The GPC column set was calibrated with 21 narrow molecular weight distribution polystyrene standards, ranging in molecular weight from 580 to 8,400,000, and arranged in 6 "cocktail" mixtures, with at least ten times the interval between individual molecular weights. Standards were purchased from Agilent Technologies. For molecular weights equal to or greater than 1,000,000, 0.025 grams of polystyrene standards were prepared in 50 milliliters of solvent, and for molecular weights less than 1,000,000, 0.05 grams of polystyrene standards were prepared in 50 milliliters of solvent. The polystyrene standards were dissolved at 80 degrees Celsius and gently stirred for 30 minutes. The polystyrene standard peak molecular weight was converted to polyethylene molecular weight using equation 1 (as described in Williams and Ward, Journal of Polymer Science (J. Polym. Sci.), Polym. Let., 6, 621 (1968)):
[0074] M 聚乙烯 =A×(M 聚苯乙烯 ) B (Equation 1)
[0075] Where M is the molecular weight, A has a value of 0.4315, and B equals 1.0.
[0076] A fifth order polynomial was used to fit the calibration points to the corresponding polyethylene equivalents.A small adjustment (approximately 0.375 to 0.445) was made to A to correct for column resolution and band broadening effects such that a linear homopolymer polyethylene standard was obtained at 120,000 Mw.
[0077] Plate counts for the GPC column set were performed using decane (prepared as 0.04 g in 50 mL TCB and dissolved for 20 minutes under slow stirring). Plate counts (Equation 2) and symmetry (Equation 3) were measured at 200 μL injection according to the following equations:
[0078]
[0079] Where RV is the retention volume in milliliters, and peak width is in milliliters, peakmax is the maximum position of the peak, tenth height is 1 / 10 of the height of the maximum peak, and where postpeak refers to the tail of the peak with a retention volume later than the maximum peak, and where frontpeak refers to the front of the peak with a retention volume earlier than the maximum peak. The plate count of the chromatographic system should be greater than 18,000, and the symmetry should be between 0.98 and 1.22.
[0080] The samples were prepared semi-automatically using the PolymerChar "Instrument Control" software, where the target weight of the sample was set to 2 mg / ml and the solvent (containing 200 ppm BHT) was added to a septum-capped vial previously sparged with nitrogen by the PolymerChar high temperature autosampler. The samples were dissolved at 160°C for 2 hours under "slow" shaking.
[0081] Based on the GPC results, the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR spectrometer was used, according to Equations 4-6, using the PolymerChar GPCOne TM The software was used to calculate the Mn of the baseline-subtracted IR chromatogram at each equidistant data collection point (i) and the polyethylene equivalent molecular weight obtained from the narrow standard calibration curve at point (i) according to Equation 1. (GPC) 、Mw (GPC) and Mz (GPC) Calculation.
[0082]
[0083] To monitor deviations over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate (flow rate (nominal)) for each sample by comparing the RV of the corresponding decane peak in the sample (RV (FM sample)) with the RV of the alkane peak in the narrow standard calibration (RV (FM calibrated)). It was then assumed that any changes in the decane marker peak time were related to linear changes in the flow rate (flow rate (effective)) throughout the run. In order to facilitate the highest accuracy measured for the RV of the flow marker peak, a least squares fitting procedure was used to fit the peak of the flow marker concentration chromatogram to a quadratic equation. The first derivative of the quadratic equation was then used to solve for the true peak position. After calibrating the system based on the flow marker peak, the effective flow rate (relative to the narrow standard calibration) was calculated as Equation 7. By PolymerCharGPCOne TM The software completes the processing of the flow marker peaks. An acceptable flow rate correction is such that the effective flow rate should be within + / - 1% of the nominal flow rate.
[0084] Flow(effective) = Flow((nominal) × (RV(FM calibration) / RV(FM sample)) (Equation 7)
[0085] The melt index (MI) (I2) in g / 10 min was measured according to ASTM D1238 (190° C. / 2.16 kg).
[0086] Unrestrained yield strength (blocking test)
[0087] Specific blocking tests were performed on inventive examples (IE) 1, 2 and 4 and comparative samples (CS) CS B (INFUSE 9507), CS D (INFUSE 9107) and CS G (INFUSE 9817) to evaluate their anti-caking behavior. The blocking test was performed according to the following procedure to measure the strength of granules that had been consolidated for a predetermined time at a known stress level and temperature. A cylinder with a diameter of 2 inches was used, consisting of two halves held together by hose clamps. A thin Teflon sheet was inserted into the cell as a lining for the cylinder wall to minimize wall friction. A 60-150 gram sample of the granules was poured into the cylinder. During loading, the side walls of the cylinder were gently tapped to settle the solids. The 2-inch The circular sheet is placed on a weight load. The test load, temperature, and test duration are set to simulate relatively harsh shipping or storage conditions. The weight load is placed on the sheet and the cylinder is placed in an oven at 37°C for a specified time interval. A 4.5 pound load is used to simulate 195 lbf / ft 2After the test interval, the load is removed and the cylinder is allowed to cool at ambient conditions for at least 12 hours. The sample is then removed from the cylinder. The tensile testing machine measures the unrestrained yield strength (UYS) in compression mode and the result is expressed in pounds per square foot (lb / ft 2 ) as the unit.
[0088] If the particles in the consolidated sample are completely free flowing, the particles will not remain in the form of a cylinder, but will only accumulate in a pile. If the consolidated mass of pellets does remain in the form of a cylinder, the maximum force required to crush the cylinder is measured using the Instron machine. The consolidated particles are crushed using the INSTRON frame to measure the maximum force required to break the "cylindrical form" of the consolidated particles. The consolidated pellets are positioned in the Instron machine in a vertical direction - the longer dimension is the vertical direction. This test uses a constant strain rate of 2 mm / min (room temperature). To ensure data consistency, each composition (coated pellets) is measured twice and the average value is reported.
[0089] The unrestrained yield strength (UYS) is calculated as follows:
[0090] UYS(lb / ft 2 ) = peak force / cross-sectional area of cylinder.
[0091] UYS indicates the blocking force (the greater the unrestrained yield strength, the greater the blocking force). A value of zero corresponds to a free-flowing pellet.
[0092] XRF
[0093] X-ray fluorescence (XRF) was performed using a Spectro-Asoma (Marble Falls, TX) Phoenix energy dispersive XRF spectrometer. The spectrometer was equipped with a Mo anode X-ray tube, a 30 kV power supply, a Mo (2 mil thick) tubular filter, an atmospheric neon sealed gas ratio detector with a 1 mil thick Be window, and operating software version 220. The spectrometer was used to obtain the Zn Kα characteristic x-ray intensity and x-ray tube backscattering intensity of samples and standards. Table A below lists the operating conditions used in the Phoenix method validation. Ethylene / octene multi-block copolymer particles were poured into an XRF sample cup (catalog number 1730) equipped with a polypropylene film (catalog number 436) obtained from Chemplex Industries. The cup was filled with particles, but not overfilled, so the particles were above the top of the cup. The film was fixed to the cup with the ring provided, and the particles were pressed on a flat surface covered with a clean, lint-free paper towel. The data were analyzed using a calibration developed based on ICP and XRF in "Analytical Sciences". The reported Zn concentration values (in parts per million, "ppm") were within + / - 10%.
[0094] Table A
[0095] DETAILED DESCRIPTION
[0096] The present disclosure provides a method. In one embodiment, a method is provided, which includes contacting ethylene and octene with a catalyst system under polymerization conditions at a temperature greater than 125° C. The catalyst system comprises (i) a first polymerization catalyst and (ii) a second polymerization catalyst, and (iii) a chain shuttling agent. The first polymerization catalyst has a structure of formula (III).
[0097] Formula (III)
[0098]
[0099] in
[0100] M is titanium, zirconium or hafnium.
[0101] Each Y 1 and Y 2 Independently selected from the group consisting of: (C1-C 40 ) hydrocarbon group, (C1-C 40 ) trihydrocarbylsilylhydrocarbyl, halogen, alkoxide or amine, or the two Y groups together are a divalent hydrocarbylene, hydrocarbondiyl or trihydrocarbylsilyl group;
[0102] Each Ar 1and Ar 2 Independently selected from the group consisting of: (C6-C 40 ) aryl, substituted (C6-C 40 ) aryl, (C3-C 40 ) heteroaryl and substituted (C3-C 40 ) heteroaryl;
[0103] T 1 is independently at each occurrence a saturated C2-C4 alkyl radical having a 1 Formation of a bridge between the two bonded oxygen atoms; and
[0104] Each R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , R 9 , R 10 , R 11 , R 12 , R 13 and R 14 are independently selected from the group consisting of hydrogen, halogen, (C1-C 40 ) alkyl, substituted (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl, substituted (C1-C 40 ) heteroalkyl, (C6-C 40 ) aryl, substituted (C6-C 40 ) aryl, (C3-C 40 ) heteroaryl and substituted (C3-C 40 ) heteroaryl and nitro (NO2). Each R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , R 9 , R 10 , R 11 , R 12 , R 13 and R 14 are independently selected from the group consisting of hydrogen, halogen, (C1-C 40 ) alkyl, substituted (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl, substituted (C1-C 40) heteroalkyl, (C6-C 40 ) aryl, substituted (C6-C 40 ) aryl, (C3-C 40 ) heteroaryl and substituted (C3-C 40 ) heteroaryl and nitro (NO2).
[0105] The second polymerization catalyst (ii) has the structure of formula (I)
[0106] Formula (I)
[0107]
[0108] in
[0109] M is titanium, zirconium or hafnium.
[0110] Each Z 1 and Z 2 Independently selected from the group consisting of: (C1-C 40 ) hydrocarbon group, (C1-C 40 ) trihydrocarbylsilylhydrocarbyl, halogen, alkoxide or amine, or the two Z groups together are a divalent hydrocarbylene, hydrocarbondiyl or trihydrocarbylsilyl group;
[0111] Each Q 1 and Q 10 Independently selected from the group consisting of: (C6-C 40 ) aryl, substituted (C6-C 40 ) aryl, (C3-C 40 ) heteroaryl and substituted (C3-C 40 ) heteroaryl;
[0112] Each Q 2 , Q 3 , Q 4 , Q 7 , Q 8 and Q 9 are independently selected from the group consisting of: hydrogen, (C1-C 40 ) alkyl, substituted (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl, substituted (C1-C 40 ) heteroalkyl, halogen and nitro (NO2);
[0113] Each Q 5 and Q 6 Independently selected from the group consisting of: (C1-C 40 ) alkyl, substituted (C1-C 40 )alkyl and [(Si)1-(C+Si) 40] substituted organosilyl;
[0114] each N is independently nitrogen;
[0115] Optionally, Q 1-5 Two or more of the groups are combined together to form a ring structure, wherein such ring structure has from 5 to 16 atoms in the ring excluding any hydrogen atoms.
[0116] Optionally, Q 6-10 Two or more of the groups may be combined together to form a ring structure, wherein such ring structure has from 5 to 16 atoms in the ring excluding any hydrogen atoms.
[0117] The catalyst system also comprises a chain shuttling agent (iii). The process comprises forming an ethylene / octene multi-block copolymer having a normalized OOO triad content greater than 0.25.
[0118] The method comprises contacting ethylene and octene with a catalyst system under polymerization conditions at a temperature greater than 125° C. As used herein, the term "polymerization conditions" refers to the process parameters for copolymerizing ethylene and octene in the presence of a catalyst system. Polymerization conditions include, for example, polymerization reactor conditions (reactor type), reactor pressure, reactor temperature, concentrations of reagents and polymers, solvents, supports, residence time and distribution, thereby affecting molecular weight distribution and polymer structure. As used herein, the term "polymerization conditions" includes polymerization temperatures greater than 125° C.
[0119] In one embodiment, the polymerization conditions include a polymerization temperature in the range of 130°C to 170°C, or 130°C to 160°C, or 140°C to 150°C.
[0120] The method comprises contacting ethylene and octene with a catalyst system under polymerization conditions at a temperature above 125° C. The catalyst system comprises (i) a first polymerization catalyst (formula (III) above), (ii) a second polymerization catalyst (formula (I) above) and (iii) a chain shuttling agent.
[0121] The catalyst system includes a chain shuttling agent. As used herein, a "chain shuttling agent" refers to a compound that can cause a polymeric radical transfer between various active catalyst sites under polymerization conditions. That is, the transfer of polymer fragments enters and exits the active catalyst site in an easy and reversible manner. In contrast to a shuttling agent or chain shuttling agent, an agent that only acts as a "chain transfer agent", such as certain main group alkyl compounds, may exchange, for example, an alkyl group on a chain transfer agent as the chain extender grows. The polymer chain on the catalyst usually results in the termination of the polymer chain growth. In this case, the main center can act as a reservoir for polymer chain failure, rather than reversibly transferring with the catalyst site in the manner of a chain shuttling agent. Ideally, the intermediate formed between the chain shuttling agent and the polymeric radical chain is not stable enough relative to the exchange between the intermediate and any other growing polymeric radical chain, making chain termination relatively rare.
[0122] The method includes forming an ethylene / octene multi-block copolymer having a normalized OOO triad content greater than 0.25. The term "ethylene / octene multi-block copolymer" refers to a copolymer consisting of ethylene and octene comonomers in polymerized form, the polymer being characterized in that multiple blocks or segments of two polymerized monomer units (i.e., ethylene and octene) are different in chemical or physical properties, and the blocks are connected (or covalently bonded) in a linear manner, i.e., a polymer containing chemically distinguishable units connected end-to-end relative to polymerized ethylenic functionality. Ethylene / octene multi-block copolymers include block copolymers having two blocks (diblocks) and more than two blocks (multiblocks). Ethylene / octene multi-block copolymers do not contain or otherwise do not include styrene (i.e., do not contain styrene), and / or vinyl aromatic monomers, and / or conjugated dienes. When the amount of "ethylene" or "octene" is mentioned in the copolymer, it is understood that this refers to its polymerized units. The ethylene / octene multi-block copolymer can be represented by the formula: (AB)n, wherein n is at least 1, preferably an integer greater than 1, such as 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100 or more, "A" represents a hard block or segment and "B" represents a soft block or segment. Preferably, A and B are connected or covalently bonded in a substantially linear manner, or in a linear manner, relative to a substantially branched or substantially star-shaped manner. In other embodiments, the A blocks and B blocks are randomly distributed along the polymer chain. In other words, the block copolymer generally does not have the following structure: AAA-AA-BBB-BB. In one embodiment, the ethylene / octene multi-block copolymer does not have a third type of block, which comprises one or more different comonomers. In another embodiment, block A and block B each have monomers or comonomers that are substantially randomly distributed within the block. In other words, neither block A nor block B comprises two or more subsegments (or subblocks) of different compositions, such as an end segment having a substantially different composition than the remainder of the block.
[0123] Ethylene accounts for most of the mole fraction of the entire ethylene / octene multi-block copolymer. Ethylene accounts for at least 50 mol% (mol%) of the entire ethylene / octene multi-block copolymer. In one embodiment, based on the total moles of the ethylene / octene multi-block copolymer, the ethylene / octene multi-block copolymer comprises 50mol% to 80mol%, or 60mol% to 80mol%, or 65mol% to 80mol%, or 85mol%, or 90mol%, or 95mol% of ethylene and the opposite amount of octene, or 5mol% to 35mol%, or 10mol% to 35mol%, or 15mol% to 35mol%, or 20mol% to 35mol%, or 40mol%, or less than 50mol% octene. In other embodiments, the ethylene / octene multi-block copolymer comprises 5mol% to 30mol% of octene (and 95mol% to 70mol% of ethylene), or 10mol% to 25mol% of octene (and 90mol% to 75mol% of ethylene).
[0124] Ethylene / octene multi-block copolymers include various amounts of "hard" segments and "soft" segments. "Hard" segments are blocks of polymerized units, wherein ethylene is present in an amount of greater than 90wt% or 95wt% or greater than 95wt% or greater than 98wt%, up to 100wt%, based on the weight of the polymer. In other words, the comonomer content (except the monomer content of ethylene) in the hard segments is less than 10wt%, or 5wt%, or less than 5wt%, or less than 2wt%, and can be as low as zero, based on the weight of the polymer. In some embodiments, the hard segments include all or substantially all units derived from ethylene. "Soft" segments are blocks of polymerized units, wherein the comonomer content (octene content) is greater than 5wt%, or greater than 8wt%, or greater than 10wt%, or greater than 15wt%, based on the weight of the polymer. In one embodiment, the comonomer content in the soft segments is greater than 20 wt% or greater than 25 wt% or greater than 30 wt% or greater than 35 wt% or greater than 40 wt% or greater than 45 wt% or greater than 50 wt% or greater than 60 wt% and up to 100 wt%.
[0125] The soft segment can be present in the base ethylene / butylene multi-block copolymer at 1wt%, or 5wt%, or 10wt%, or 15wt%, or 20wt%, or 25wt%, or 30wt%, or 35wt%, or 40wt%, or 45wt% to 55wt%, or 60wt%, or 65wt%, or 70wt%, or 75wt%, or 80wt%, or 85wt%, or 90wt%, or 95wt%, or 99wt% of the total weight of the ethylene / octene multi-block copolymer. In contrast, the hard segment can be present in a similar range. The soft segment weight percentage and the hard segment weight percentage can be calculated based on data obtained from DSC or NMR. This method and calculation are disclosed in, for example, USP 7,608,668, the disclosure of which is incorporated herein by reference in its entirety. Specifically, the weight percentages of the hard and soft segments and the melting temperature (SS-Tm) of the soft segment can be determined as described in columns 57 to 63 of USP 7,608,668, which is incorporated herein by reference.
[0126] Ethylene / octene multi-block copolymers comprise two or more chemically distinct regions or segments (referred to as "blocks") joined (or covalently bonded) in a linear manner, i.e., polymers containing chemically distinguishable units joined end-to-end in terms of polymerized olefinic functionality rather than joined in a pendant or grafted manner. Blocks differ in the amount or type of comonomer incorporated, density, amount of crystallinity, crystallite size attributable to polymers of such composition, type or degree of stereoisomerism (isotactic or syndiotactic), regioregularity or regio-irregularity, amount of branching (including long chain branching or hyperbranching), homogeneity, or any other chemical or physical characteristic. Compared to prior art block interpolymers, including those produced by sequential monomer addition, stereolabile catalysts, or anionic polymerization techniques, the inventive ethylene / octene multi-block copolymers are characterized by a unique distribution of polymer polydispersity (PDI or Mw / Mn or MWD), polydisperse block length distribution, and / or polydisperse block number distribution, which, in one embodiment, is due to the effect of one or more shuttling agents in combination with various catalysts used in their preparation.
[0127] In one embodiment, the ethylene / octene multi-block copolymer is produced in a continuous process and has a polydispersity index (Mw / Mn) of 1.7 to 3.5, or 1.8 to 3, or 1.8 to 2.5, or 1.8 to 2.2. When prepared in a batch or semi-batch process, the ethylene / octene multi-block copolymer has a Mw / Mn of 1.0 to 3.5, or 1.3 to 3, or 1.4 to 2.5, or 1.4 to 2.
[0128] In addition, the ethylene / octene multi-block copolymer has a PDI (or Mw / Mn) that fits the Schultz-Flory distribution rather than the Poisson distribution. The ethylene / octene multi-block copolymer of the present invention has both a polydisperse block distribution and a polydisperse distribution of block sizes. This results in the formation of polymer products with improved and distinguishable physical properties. The theoretical benefits of a polydisperse block distribution have been previously described in Potemkin, Physical Review E( Physical Review E )(1998) 57(6), pp. 6902-6912 and Dobrynin, Journal of Chemical Physics ( J.Chem.Phvs.) (1997) 107(21), pp. 9234-9238.
[0129] In one embodiment, the ethylene / octene multi-block copolymers of the present invention have a most probable distribution of block lengths.
[0130] The process forms ethylene / octene multi-block copolymers having a normalized OOO triad content greater than 0.25.
[0131] In one embodiment, the process comprises forming an ethylene / octene multi-block copolymer having a normalized OOO triad content of from 0.30 to 0.75, or from 0.30 to 0.70, or from 0.35 to 0.70.
[0132] In one embodiment, the process comprises contacting ethylene and octene with a catalyst system under polymerization conditions at a temperature of 130° C. to 170° C. The catalyst system comprises (i) a first polymerization catalyst which is hafnium, [[2′,2″′-[1,4-butanediylbis(oxy-κO)]bis[3-(9H-carbazol-9-yl)-5-(1,1-dimethylnonyl)-5′-fluoro[1,1′-biphenyl]-2-phenol-κO]](2-)]dimethyl-, and has the structure of catalyst 1.
[0133] Catalyst 1
[0134]
[0135] (ii) a second polymerization catalyst which is hafnium, dimethylbis[N-(2-methylpropyl)-6-(2,4,6-trimethylphenyl)-2-pyridinylamino-κN1,κN2]-, and has the structure of Catalyst 2
[0136] Catalyst 2
[0137] and
[0138] (iii) a chain shuttling agent, which is diethyl zinc. The method includes forming an ethylene / octene multi-block copolymer having a hard segment and a soft segment. The soft segment has a soft segment melting temperature (SS-Tm) of -30°C to 35°C or -30°C to 30°C, and the ethylene / octene multi-block copolymer has a first TGIC peak temperature (T p1 ) and the second TGIC peak temperature (T p2 ), where T p2 Satisfies equation (A)
[0139] T p2 ≤0.0068×(SS-Tm) 2 +0.07×(SS-Tm)+73.2. Equation (A)
[0140] The present disclosure provides compositions formed by the aforementioned polymerization methods.In one embodiment, the composition includes an ethylene / octene multi-block copolymer having a normalized OOO triad content greater than 0.25.
[0141] In one embodiment, the composition includes an ethylene / octene multi-block copolymer having a normalized OOO triad content of from 0.30 to 0.75, or from 0.30 to 0.70, or from 0.35 to 0.70.
[0142] In one embodiment, the ethylene / octene multi-block copolymer of the composition comprises 10 mol% to 30 mol% octene and an equal amount of ethylene or 90 mol% to 70 mol% ethylene, based on the total moles of the ethylene / octene multi-block copolymer.
[0143] In one embodiment, the ethylene / octene multi-block copolymer of the composition has a hard segment and a soft segment, and the soft segment has a soft segment melting temperature (SS-Tm) of -30°C to 35°C, or -30°C to 30°C. The ethylene / octene multi-block copolymer has a first TGIC peak temperature (T p1 ) and the second TGIC peak temperature (T p2 ), where Tp2 satisfies equation (A)
[0144] T p2 ≤0.0068×(SS-Tm) 2 +0.07×(SS-Tm)+73.2. Equation (A)
[0145] In one embodiment, the ethylene / octene multi-block copolymer of the composition satisfies equation (A) and has a T in the range of 125°C to 150°C. p1 and T in the range of 54°C to 96°C or 68°C to 90°C p2 .
[0146] In one embodiment, the ethylene / octene multi-block copolymer has a glass transition temperature (Tg) of -70°C to -55°C, or -67°C to -57°C.
[0147] In one embodiment, the ethylene / octene multi-block copolymer of the composition has a density from 0.855 g / cc to 0.890 g / cc.
[0148] In one embodiment, the ethylene / octene multi-block copolymer of the composition has a Tm of 115°C to 125°C, or 118°C to 123°C.
[0149] In one embodiment, the ethylene / octene copolymer of the composition has a melt index (I2) of 0.1 g / 10 min to 35.0 g / 10 min, or 0.5 g / 10 min to 32 g / 10 min, or 1.0 g / 10 min to 17 g / 10 min.
[0150] In one embodiment, the ethylene / octene multi-block copolymer of the composition has an elastic recovery (Re) of 50%, or 60% to 70%, or 80%, or 90% at a temperature of 21° C. and a deformation rate of 300% / min.
[0151] In one embodiment, the ethylene / octene multi-block copolymer of the composition has a polydisperse distribution of blocks and a polydisperse distribution of block sizes.
[0152] In one embodiment, the unrestrained yield strength (UYS) of the ethylene / octene multi-block copolymer of the composition at 21°C is 0 lb / ft after two months. 2 To less than 200lb / ft 2 In another embodiment, the unrestrained yield strength (UYS) of the ethylene / octene multi-block copolymer of the composition at 21°C is 0 lb / ft after two months. 2 To less than 200lb / ft 2 , or 0 lb / ft after two months 2 To less than 100lb / ft 2 , or 0 lb / ft after two months 2 To less than 50lb / ft 2 , or 0 lb / ft after two months 2 To less than 10lb / ft 2 , or 0 lb / ft after two months 2 To less than 5lb / ft 2 , or greater than 0 lb / ft2 to less than 5 lb / ft2 after two months 2 .
[0153] In one embodiment, the unconstrained yield strength (UYS) of the ethylene / octene multi-block copolymer of the composition at 0°C is 0 lb / ft after two months. 2 To less than 73lb / ft 2 In another embodiment, the unrestrained yield strength (UYS) of the ethylene / octene multi-block copolymer of the composition at 0°C is 0 lb / ft after two months. 2 To less than 54lb / ft 2 , or the unrestrained yield strength (UYS) at 0°C is 0 lb / ft after two months 2 .
[0154] In one embodiment, the ethylene / octene multi-block copolymer of the composition has a funnel flow rate of greater than 150 g / s to 200 g / s after 6 weeks.
[0155] In one embodiment, the ethylene / octene multi-block copolymer of the composition consists only of ethylene and octene comonomers and has one, some or all of the following properties:
[0156] (i) a normalized OOO triplet value of 0.35 to 0.70; and / or
[0157] (ii) 10 mol% to 30 mol% octene and 90 mol% to 70 mol% ethylene; and / or
[0158] (iii) SS Tm of -30°C to 35°C or -30°C to 30°C, where T p2 ≤0.0068×(SS-Tm) 2 +0.07×(SS-Tm)+73.2; and / or
[0159] (iv)T p1 is 125°C to 150°C, and T p2 54°C to 96°C or 68°C to 90°C; and / or
[0160] (v) a Tg of -70°C to -55°C; and / or
[0161] (vi) a density of 0.855 g / cc to 0.890 g / cc; and / or
[0162] (vii) a Tm of 115°C to 125°C; and / or
[0163] (viii) a melt index (I2) of 0.1 g / 10 min to 20.0 g / 10 min; and / or
[0164] (ix) an elastic recovery (Re) of 50% to 90%; and / or
[0165] (x) Mw / Mn of 1.7 to 3.5; and / or
[0166] (xi) polydispersity of blocks and polydispersity of block sizes; and / or
[0167] (xii) Unrestrained Yield Strength (UYS) at 21°C is 0 lb / ft after two months 2 To less than 5lb / ft 2 ; and / or
[0168] (xiii) The funnel flow rate is greater than 150 g / s to 200 g / s.
[0169] The ethylene / octene multi-block copolymers of the present invention described herein can be used in many applications. Due to the improved handling of particles and the lower tendency of the particles to adhere to themselves (stickiness), the ethylene / octene multi-block copolymers of the present invention disclosed herein are beneficial to film applications (such as cast films for elastic films). For example, the improved viscosity enables the commercialization of lower overall density, increased soft segment comonomer content and / or higher melt flow products, which provides better elastic hysteresis and retraction behavior in films (such as cast films).
[0170] The inventive ethylene / octene multi-block copolymers described herein can also be used in foam applications (e.g., for footwear midsole foam applications). The sole foam made from the inventive ethylene / octene multi-block copolymers provides improved softness for athletic shoes and improved resilience from the soft segment components of the inventive ethylene / octene multi-block copolymers.
[0171] The present invention also specifically relates to the following embodiments:
[0172] 1. A method, comprising:
[0173] Under polymerization conditions, at a temperature above 125°C, ethylene and octene are contacted with a catalyst system comprising:
[0174] (i) A first polymerization catalyst having a structure of formula (III)
[0175] Formula (III)
[0176]
[0177] in
[0178] M is titanium, zirconium or hafnium;
[0179] Each Y 1 and Y 2 Independently selected from the group consisting of: (C1-C 40 ) hydrocarbon group, (C1-C40 ) trihydrocarbylsilylhydrocarbyl, halogen, alkoxide or amine, or the two Y groups together are a divalent hydrocarbylene, hydrocarbondiyl or trihydrocarbylsilyl group;
[0180] Each Ar 1 and Ar 2 Independently selected from the group consisting of: (C6-C 40 ) aryl, substituted (C6-C 40 ) aryl, (C3-C 40 ) heteroaryl and substituted (C3-C 40 ) heteroaryl;
[0181] T 1 is independently at each occurrence a saturated C2-C4 alkyl radical, said alkyl radical being in T 1 A bridge is formed between the two bonded oxygen atoms; and
[0182] Each R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , R 9 , R 10 , R 11 , R 12 , R 13 and R 14 are independently selected from the group consisting of hydrogen, halogen, (C1-C 40 ) alkyl, substituted (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl, substituted (C1-C 40 ) heteroalkyl, (C6-C 40 ) aryl, substituted (C6-C 40 ) aryl, (C3-C 40 ) heteroaryl and substituted (C3-C 40 ) heteroaryl and nitro (NO2);
[0183] (ii) a second polymerization catalyst having a structure of formula (I)
[0184] Formula (I)
[0185]
[0186] in
[0187] M is titanium, zirconium or hafnium,
[0188] Each Z 1 and Z2 Independently selected from the group consisting of: (C1-C 40 ) hydrocarbon group, (C1-C 40 ) trihydrocarbylsilylhydrocarbyl, halogen, alkoxide or amine, or the two Z groups together are a divalent hydrocarbylene, hydrocarbondiyl or trihydrocarbylsilyl group;
[0189] Each Q 1 and Q 10 Independently selected from the group consisting of: (C6-C 40 ) aryl, substituted (C6-C 40 ) aryl, (C3-C 40 ) heteroaryl and substituted (C3-C 40 ) heteroaryl;
[0190] Each Q 2 , Q 3 , Q 4 , Q 7 , Q 8 and Q 9 are independently selected from the group consisting of: hydrogen, (C1-C 40 ) alkyl, substituted (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl, substituted (C1-C 40 ) heteroalkyl, halogen and nitro (NO2);
[0191] Each Q 5 and Q 6 Independently selected from the group consisting of: (C1-C 40 ) alkyl, substituted (C1-C 40 )alkyl and [(Si)1-(C+Si) 40 ] substituted organosilyl;
[0192] each N is independently nitrogen;
[0193] Optionally, the Q 1-5 Two or more of the groups combine together to form a ring structure, wherein such ring structure has from 5 to 16 atoms in the ring excluding any hydrogen atoms; and
[0194] Optionally, the Q 6-10 Two or more of the groups may be combined together to form a ring structure, wherein such ring structure has from 5 to 16 atoms in the ring excluding any hydrogen atoms; and
[0195] Optionally, the Q 6-10Two or more of the groups may be combined together to form a ring structure, wherein such ring structure has from 5 to 16 atoms in the ring excluding any hydrogen atoms;
[0196] (iii) a chain shuttling agent; and
[0197] An ethylene / octene multi-block copolymer having a normalized OOO triad content greater than 0.25 is formed.
[0198] 2. The method according to claim 1, comprising contacting the ethylene and octene with a catalyst system under polymerization conditions at a temperature of 130°C to 170°C, the catalyst system comprising:
[0199] (i) A first polymerization catalyst having the structure of catalyst 1
[0200] Catalyst 1
[0201]
[0202] (ii) A second polymerization catalyst having the structure of Catalyst 2
[0203] Catalyst 2
[0204] as well as
[0205] (iii) a chain shuttling agent which is diethylzinc; and
[0206] An ethylene / octene multi-block copolymer having a hard segment and a soft segment is formed; the soft segment has a soft segment melting temperature (SS-Tm) of -30°C to 30°C, and the ethylene / octene multi-block copolymer has a first TGIC peak temperature (T p1 ) and the second TGIC peak temperature (T p2 ),
[0207] Where T p2 Satisfies equation (A)
[0208] T p2 ≤0.0068×(SS-Tm) 2 +0.07×(SS-Tm)+73.2.
[0209] 3. A composition comprising:
[0210] Ethylene / octene multi-block copolymers having a normalized OOO triad content greater than 0.25.
[0211] 4. The composition of item 3, wherein the ethylene / octene multi-block copolymer comprises 10 mol% to 30 mol% octene.
[0212] 5. A composition according to item 4, wherein:
[0213] The ethylene / octene multi-block copolymer comprises a hard segment and a soft segment; the soft segment has a soft segment melting temperature (SS-Tm) of -30°C to 30°C, and the ethylene / octene multi-block copolymer has a first TGIC peak temperature (T p1 ) and the second TGIC peak temperature (T p2 ),
[0214] Where T p2 Satisfies equation (A)
[0215] T p2 ≤0.0068×(SS-Tm) 2 +0.07×(SS-Tm)+73.2.
[0216] 6. The composition according to claim 5, wherein the ethylene / octene multi-block copolymer has a T of 125°C to 150°C. p1 and T of 68°C to 90°C p2 .
[0217] 7. The composition according to item 6, wherein the glass transition temperature (Tg) of the ethylene / octene multi-block copolymer is from -70°C to -55°C.
[0218] 8. The composition of item 7, wherein the ethylene / octene multi-block copolymer has a density of 0.855 to 0.890 grams per cubic centimeter (g / cc).
[0219] 9. The composition of claim 8, wherein the ethylene / octene multi-block copolymer has an unconstrained yield strength (UYS) at 21°C of 0 lb / ft after two months. 2 To less than 200lb / ft 2 .
[0220] 10. The composition according to any one of items 8 to 9, wherein the ethylene / octene multi-block copolymer has a funnel flow rate of greater than 150 g / s to 200 g / s after 6 weeks.
[0221] 11. The composition according to any one of items 8 to 10, wherein the unconstrained yield strength (UYS) of the ethylene / octene multi-block copolymer at 0°C is 0 lb / ft after two months. 2 To less than 73lb / ft 2 .
[0222] By way of example and not limitation, some embodiments of the present disclosure are described in detail in the following examples.
[0223] Example
[0224] Table 1 below provides the catalysts, co-catalysts, and chain shuttling agents used to prepare Comparative Sample (CS) A and Inventive Examples (IE) 1-7.
[0225] Table 1 - Materials
[0226]
[0227]
[0228] Aggregation of CS A and IE 1-7
[0229] All raw materials (ethylene and octene) and process solvents (narrow boiling range high purity isoparaffin solvent, Isopar-E) were purified with molecular sieves before introduction into the reaction environment. Hydrogen was supplied under pressure in high purity grades without further purification. The reactor monomer feed stream was pressurized to greater than the reaction pressure via a mechanical compressor. The solvent and comonomer feed were pressurized to greater than the reaction pressure via a pump. Each catalyst component was manually diluted in batches with the purified solvent and pressurized to greater than the reaction pressure. All reaction feed streams were measured with mass flow meters and independently controlled with a computer automated control system.
[0230] The continuous solution polymerization reactor is composed of a non-adiabatic isothermal circulating loop reactor full of liquid that simulates a continuous stirred tank reactor (CSTR) with heat removal. All fresh solvents, monomers, comonomers, hydrogen and catalyst component feeds can be controlled independently. By passing the feed stream through a heat exchanger, the total fresh feed stream (solvent, monomer, comonomer and hydrogen) to the reactor is temperature-controlled to maintain a single solution phase. The total fresh feed to the polymerization reactor is injected into the reactor at two locations, wherein the reactor volume between each injection position is roughly equal. The fresh feed is controlled by receiving half of the total fresh feed mass flow rate with each injector. The catalyst component is injected into the polymerization reactor through a specially designed injection plug. The computer controls the first polymerization catalyst component feed (catalyst A and catalyst 1 in Table 1) to maintain the reactor monomer conversion under a specified target. The molar ratio of the second polymerization catalyst feed (catalyst B and catalyst 2 in Table 1) and the total catalyst feed is regulated to maintain the desired separation between the polymer soft segment and the hard segment. The cocatalyst components (cocatalyst 3 and cocatalyst-4 from Table 1) are fed based on the calculated specified molar ratio with the catalyst component. Immediately following each reactor feed injection position, the feed stream is mixed with the circulating polymerization reactor contents with a static mixing element. The contents of the reactor are continuously circulated through a heat exchanger, which is responsible for removing a large amount of reaction heat, and wherein the temperature on the coolant side is responsible for maintaining the isothermal reaction environment at a specified temperature. The circulation around the reactor loop is provided by a pump.
[0231] The reactor effluent enters a zone where it is deactivated by adding and reacting with a suitable reagent (water). At this same reactor outlet location, other additives are added for polymer stabilization. After the catalyst is deactivated and the additives are added, the reactor effluent enters a devolatilization system where the polymer is removed from the non-polymer stream. The separated polymer melt is granulated and collected. The non-polymer stream passes through various devices that separate most of the ethylene removed from the system. Most of the solvent and unreacted comonomer are recycled back to the reactor after passing through the purification system. Small amounts of solvent and comonomer are removed from the process.
[0232] The polymerization conditions for comparative sample (CS) CS A and inventive examples (IE) IE 1-7 are provided in Table 2 below.
[0233] Table 2 - Polymerization conditions of CS A and IE 1-7
[0234]
[0235]
[0236] The polymerization conditions described above and shown in Table 2 produced ethylene / octene multi-block copolymers CS A and IE 1-7. Ethylene / octene multi-block copolymers CS A and IE 1-7 were then compared to conventional ethylene / octene multi-block copolymers sold under the trade name INFUSE. Table 3 below provides conventional ethylene / octene multi-block copolymers.
[0237] Table 3 Conventional ethylene / octene multi-block copolymers
[0238] Material supplier describe CS B The Dow Chemical Company <![CDATA[INFUSE TM 9507,0.866g / cc,5MI]]> CS C The Dow Chemical Company <![CDATA[INFUSE TM 9010,0.877g / cc,0.5MI]]> C S D The Dow Chemical Company <![CDATA[INFUSE TM 9107,0.866g / cc,1MI]]> CSE The Dow Chemical Company D9130.05, 0.885 g / cc, 1.5 MI CSF The Dow Chemical Company <![CDATA[INFUSE TM 9077,0.869g / cc,0.5MI]]> CS G The Dow Chemical Company <![CDATA[INFUSE TM 9817,0.877g / cc,15MI]]>
[0239] Figure 2 The characteristics of CS A and IE 1-7 and CS BG in Table 3 are shown in Table 4 below.
[0240]
[0241] When compared to the ethylene / octene multi-block copolymers of comparative samples CS A, CS B, CS C, CS D, CS E, CS F and CS G having the same density, MI and SS Tm design targets, the ethylene / octene multi-block copolymers of IE 1, IE 2, IE 3, IE 4, IE 5, IE 6 and IE 7 have higher total octene content. In general, polyethylene copolymers having the same density will have the same comonomer content. When IE 1-7 are compared to comparative samples AG, the ethylene / octene multi-block copolymers of IE 1-7 produced with the catalyst 1 / catalyst 2 system and polymerization conditions at a temperature above 125°C (or a temperature in the range of 130°C to 150°C) contain different comonomer distributions along the polymer backbone, which are evident in the EOE, EOO and OOO sequences. The density, MI and SS Tm of IE 1 and CS D are similar. However, when compared to Comparative Sample D (0.06 normalized OOO triplet), Inventive Example 1 showed a more than 6-fold increase in normalized OOO triplet content (0.40 normalized OOO triplet).
[0242] The density and MI are similar for IE 2 and CS B. However, Inventive Example 2 shows a 5-fold increase in normalized OOO triplet content (0.35 normalized OOO triplet) when compared to Comparative Sample B (0.07 normalized OOO triplet).
[0243] The density, MI and SS Tm of IE 3 and CS C are similar. However, Inventive Example 3 shows a 2-fold increase in normalized OOO triplet content (0.36 normalized OOO triplet) when compared to Comparative Sample C (0.14 normalized OOO triplet).
[0244] The density, MI and SS Tm are similar for IE 4 and CS G. However, Inventive Example 4 shows a 6-fold increase in normalized OOO triplet content (0.46 normalized OOO triplet) when compared to Comparative Sample G (0.07 normalized OOO triplet).
[0245] The density, MI, and SS Tm of IE 5 and CS E are similar. However, Inventive Example 5 shows a 3-fold increase in normalized OOO triplet content (0.59 normalized OOO triplet) when compared to Comparative Sample E (0.16 normalized OOO triplet).
[0246] The density, MI, and SS Tm of IE 6 and CS A are similar. However, Inventive Example 6 shows an approximately 5-fold increase in normalized OOO triplet content (0.44 normalized OOO triplet) when compared to Comparative Sample A (0.09 normalized OOO triplet).
[0247] The density, MI and SS Tm of IE 7 and CS F are similar. However, Inventive Example 7 shows a 3-fold increase in normalized OOO triplet content (0.68 normalized OOO triplet) when compared to Comparative Sample F (0.20 normalized OOO triplet).
[0248] The higher total octene content and the increased likelihood of octene monomers being inserted adjacent to each other are expected to result in poor solid handling properties for the inventive examples when compared to the comparative samples, i.e., the inventive examples are expected to be more "sticky" than the comparative samples. However, the applicant has discovered that the ethylene / octene multi-block copolymers of IE 1, IE 2, and IE 4 unexpectedly have improved solid handling properties compared to conventional ethylene / octene multi-block copolymers similar in density, MI, and SS Tm. Table 4 shows that IE 1 has a lower UYS and a higher FF compared to CS D; IE 2 has a lower UYS and a higher FF compared to CS B; and IE 4 has a lower UYS compared to CS G.
[0249] It is particularly intended that the present disclosure is not limited to the embodiments and descriptions contained herein, but includes modifications of those embodiments including parts of the embodiments and combinations of elements of different embodiments as appear within the scope of the following claims.
Claims
1. A film comprising a composition comprising: Ethylene / octene multi-block copolymers having a normalized OOO triad content greater than 0.
25.
2. The film of claim 1, wherein the ethylene / octene multi-block copolymer comprises 10 mol% to 30 mol% octene.
3. The membrane according to claim 2, wherein: The ethylene / octene multi-block copolymer comprises a hard segment and a soft segment; the soft segment has a soft segment melting temperature (SS-Tm) of -30°C to 30°C, and the ethylene / octene multi-block copolymer has a first TGIC peak temperature (T p1 ) and the second TGIC peak temperature (T p2 ), Where T p2 Satisfies equation (A) T p2 ≤0.0068×(SS-Tm) 2 +0.07×(SS-Tm)+73.2。 4. The film of claim 3, wherein the ethylene / octene multi-block copolymer has a T of 125°C to 150°C. p1 and T of 68°C to 90°C p2 .
5. The film of claim 4, wherein the ethylene / octene multi-block copolymer has a glass transition temperature (Tg) of -70°C to -55°C.
6. The film of claim 5, wherein the ethylene / octene multi-block copolymer has a density of 0.855 to 0.890 grams per cubic centimeter (g / cc).
7. The film of claim 6, wherein the ethylene / octene multi-block copolymer has an unconstrained yield strength (UYS) at 21°C of 0 lb / ft after two months. 2 To less than 200lb / ft 2 .
8. The film according to claim 6 or 7, wherein the ethylene / octene multi-block copolymer has a funnel flow rate of greater than 150 g / s to 200 g / s after 6 weeks.
9. The film of any one of claims 6 to 8, wherein the ethylene / octene multi-block copolymer has an unconstrained yield strength (UYS) at 0°C of 0 lb / ft after two months. 2 To less than 73lb / ft 2 .
10. The film according to any one of claims 1 to 9, wherein the film is a cast film.
Citation Information
Patent Citations
Chromatography of polymers
EP2714226B1
Ethylene / alpha-olefins block interpolymers
US7608668B2
Chromatography of polyolefin polymers
US8318896B2
Chromatography of polyolefin polymers
US8476076B2